Clinical Consensus Statement: Pediatric Chronic Rhinosinusitis. (October 2014) - Brietzke, Scott E.; Shin, Jennifer J.; Choi, Sukgi; Lee, Jivianne T.; Parikh, Sanjay R.; Pena, Maria; Prager, Jeremy D.; Ramadan, Hassan; Veling, Maria; Corrigan, Maureen; Rosenfeld, Richard M.
Objective: To develop a clinical consensus statement on the optimal diagnosis and management of pediatric chronic rhinosinusitis (PCRS). Methods: A representative 9-member panel of otolaryngologists with no relevant conflicts of interest was assembled to consider opportunities to optimize the diagnosis and management of PCRS. A working definition of PCRS and the scope of pertinent otolaryngologic practice were first established. Patients of ages 6 months to 18 years without craniofacial syndromes or immunodeficiency were defined as the targeted population of interest. A modified Delphi method was then used to distill expert opinion into clinical statements that met a standardized definition of consensus. Results: After 2 iterative Delphi method surveys, 22 statements met the standardized definition of consensus while 12 statements did not. Four statements were omitted due to redundancy. The clinical statements were grouped into 4 categories for presentation and discussion: (1) definition and diagnosis of PCRS, (2) medical treatment of PCRS, (3) adenoiditis/adenoidectomy, and (4) endoscopic sinus surgery (ESS)/turbinoplasty. Conclusion: Expert panel consensus may provide helpful information for the otolaryngologist in the diagnosis and management of PCRS in uncomplicated pediatric patients.